Beberapa Faktor yang Berhubungan dengan Penggunaan Garam Beriodium Ibu Rumah Tangga di Desa Kecepak Kecamatam Batang Kabupaten Batang - Anie Nisfulaeli; Djamaludin Ramlan; Slamet Budiyanto (Universitas Pekalongan, 2010)
Background : socialize the Iodium salt consumption,was one way to control the problem lack of Iodium. The aims of this research was to knowed factors that related with consumption of Iodium salt in the housewife in Kecepak village, Batang regency. Methode : it was Descriptive correlation research with approach of cross sectional. sample in this research involved 158 housewife. It used Chi-Square statistic test to saw the correlations factors that related with consumption of Iodium salt in the housewife in Kecepak village, Batang regency. Result : showed that degree of participant knowledge was 79,1% responden understanding Iodium salt, 94,9% availability of Iodium salt, 57,6% positif perceptions to history of disease, and 92,4% responden used the Iodium salt. Bivariate analize showed knowledge about Iodium salt, and history of disease perceptions have relations with Iodium salt consumptions. Advised for all of the housewife always used Iodium salt dan increase Iodium salt consumptions. Key word : housewife, Iodium salt.